North Korean statistics and research on the North Korean economy - Suk Lee; Byungkoo Cho (Korea Development Institute (KDI), 2021)
For researchers who study the North Korean economy, one of the most unknown and interesting areas is North Korean statistics. There are many questions such as: Do statistics on the North Korean economy even exist? If not, how do overseas researchers conduct their studies? and If so, can we trust them? What statistics are published by the South Korean government and other global institutions? The list goes on, but no one has come up with a conclusive answer. This is why we chose North Korean statistics as the first topic of the new series. Numerous questions were dealt with on the topic and their significance for studies on the North Korean economy. We hope you find this article useful and informative.
Keywords: 330; Statistische Daten; Volkswirtschaft; Nordkorea